Trends of Digitalization in the Training of Teachers in the Republic of Poland - Stoika, Olesia (Educological discourse, 2023)
The article defines the trends of digitalization in the training of teachers in the Republic of Poland. It concludes that modern education must keep up with the changing world by focusing on shaping teachers’ digital competencies, personalizing teaching, using digital technologies and learning tools, actively implementing blended learning, lifelong learning, and project-based learning. By integrating and adopting these trends into the educational process in higher education institutions, future teachers will be better prepared for their future professional careers and will be able to respond to the challenges of the modern job market. Digital tools that influence the new role of the university include platforms and applications that facilitate distance learning and contribute to a paradigm shift in teaching and learning at higher education institutions. The article also explores the active use of Massive Open Online Courses (MOOCs) in the Republic of Poland. To achieve the research goals and objectives a combination of general scientific methods are used in the study, including theoretical methods such as analysis and synthesis to determine the main directions of research on the peculiarities of digitalization of teachers’ training in Poland; empirical methods to study the regulatory and legal framework of the digitalization, the works of domestic and foreign researchers regarding the digitalization of teachers’ training and education in general; and statistical processing of research results to obtain quantitative and qualitative data. Since the issue of digitalization trends in the training of teachers in the Republic of Poland is insufficiently studied, further research on the chosen problem is relevant and timely. It will contribute to adopting all the current positive trends in the educational space of Ukraine.